A Beaded Scarab in the Victoria and Albert Museum. Issue 2 (December 2019) - Hinson, Benjamin
This article is the publication of a beaded scarab from a mummy-net, excavated at Lahun in 1889–90 and donated to the Victoria and Albert Museum.